Think JBJS - Mohit Bhandari (Journal of Bone and Joint Surgery, 2025)
Orthopaedic practice is increasingly shaped by evidence-based guidelines, quality metrics, documentation requirements, insurer authorization pathways, and medicolegal scrutiny. These developments have improved care in important ways, but they may also narrow the space for individualized clinical reasoning when protocols are applied too rigidly. This Viewpoint argues that orthopaedic judgment should be understood not as a license to depart casually from evidence-based care, nor as a defense of paternalism, but as the professional capacity to integrate evidence, clinical context, and patient preferences through shared decision-making. I suggest that the standard of care is best conceptualized as transparent, well-documented, context-sensitive reasoning. When several reasonable options exist, the task of the surgeon is to help patients navigate uncertainty, tradeoffs, and real-world constraints rather than to simply default to the most defensible-looking protocol. Examples from osteoarthritis, distal radial fracture care, and complex trauma illustrate how judgment remains necessary even in an era of guidelines and metrics. The surgeon-jurist, as a conceptual figure, reminds us that responsible care depends not only on evidence and accountability but also on deliberation, communication, and discretion.